TILDA TERMINLARNING KOGNITIV TAHLILI («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article presents the theory of cognitive-comparative analysis of English and Uzbek proverbs, components of the theory and examples of comparative-cognitive analysis of English and Uzbek folk proverbs.
Keywords: proverbs, paremiology, comparative-cognitive analysis, Great chain metaphor